تشغيل الخيوط المعدنية على ماكينات النسيج ذات ضغط الهواء النفاث مع خفض عدد الفونيات المساعدة - القبيصي، أسامة محروس; محمد، شريف محمود; درغام، محمد السعيد (الجمعية العربية للحضارة والفنون الإسلامية, 2020)
مع كثرة استخدام الخيوط المعدنية كلحمات لإنتاج أقمشة مفروشات كأقمشة الستائر ومع انتشار استخدام ماكينات النسيج ذات ضغط الهواء النفاث لما لها من إمكانيات ومميزات هائلة. وهناك اعتقاد سائد بصعوبة الوسيط الهوائي (الهواء المضغوط) المستخدم بهذه الماكينات لحمل الخيوط المعدنية عبر بحر المنسوج لإتمام عملية قذف اللحمة وذلك لعدم توافر خاصية التشعير وثقل هذه اللحمات ولذلك فإنه لإنتاج مثل هذه النوعية من الأقمشة على هذه الماكينات يقوم القائمون على التصنيع باستخدام الضغوط العالية بالفونيات المساعدة واستخدام كامل الفونيات المساعدة المتوافرة بالماكينة لإنتاج هذه النوعية من الأقمشة. مما يعرض هذه القطع للتلف بسرعة لكثرة استخدامها بالشكل الخاطئ حيث يحدث لها تأكل وانسداد لهذه الفونيات والأجزاء الملحقة بها. ومع زيادة سعر العملة الصعبة مقابل العملة المحلية لتحرير سعر الصرف أصبح هناك عائق لدى مصانع النسيج في استيراد قطع الغيار وتوافر الإكسسوارات الخاصة للماكينات ولاحتياج ماكينات النسيج ذات ضغط الهواء النفاث لاستبدال بعض القطع باستمرار نتيجة كثرة استهلاكها مثل (الفونيات المساعدة والإكسسوارات الخاصة بها) وخصوصاً مع الضغوط العالية التي تؤدى إلى انسدادها واستهلاكها بسرعة مما يكون أمام المصنع إما استيراد هذه القطع بأسعار عالية مما يزيد من تكلفة التشغيل أو إيقاف الماكينات عن العمل لعدم توافر هذه القطع. ولذلك في هذا البحث قمنا بمحاولة لإنتاج أقمشة ستائر بعدد 9 عينات معتمدة على الخيوط المعدنية كلحمات على ماكينات النسيج ذات ضغط الهواء النفاث مع إيقاف بعض الفونيات المساعدة المتوافرة بالماكينة عن العمل مع استخدام ضغط (2.5 بار) مما يؤدى إلى عدم استهلاك الفونيات المساعدة وإكسسواراتها بسرعة مما يؤدى إلى تقليل تكلفة التشغيل. ومن أهم النتائج التي تم الوصول إليها أن الأقمشة المنتجة بعدد فونيات 30 فونية مساعدة قد سجلت أعلى قراءات لكل من قوة الشد في اتجاه اللحمة – وزن المتر المربع - من الأقمشة المنتجة عند عدد 40 فونية مساعدة وأخيرًا 50 فونية مساعدة والتي لها نفس المواصفات التنفيذية فنستنتج وجود علاقة عكسية بين عدد الفونيات المساعدة وقراءات قوة الشد في اتجاه اللحمة – وزن المتر المربع – للأقمشة التي لها نفس المواصفات التنفيذية.
With the frequent use of metallic yarns as wefts for the production of furniture fabrics such as curtain fabrics and with the spread of the use of air – jet looms because of its enormous potential and advantages widespread belief in the difficulty of the air medium (compressed air) used in these machines to carry metallic yarns through the woven sea to complete the process of weft extrusion because of the lack of property and the weight of these wefts, therefore, to produce such types of fabrics on these machines Auxiliary and full use of the relay nozzles available in the machine to produce this type of fabric . which exposes these pieces to damage quickly to the many used in the wrong form where it happens to eat and blockage of these relay nozzles and parts attached to it. with the increase in the price of hard currency against the local currency to liberalize the exchange rate, there is an obstacle for textile factories in importing spare parts and the availability of special accessories for machines and the need for air – jet looms to replace some parts continuously due to the high consumption such as (relay nozzles and accessories), especially with pressures. High prices that lead to blockage and consumption quickly, which is in front of the factory to either import these parts at high prices, which increases the cost of operation or stop the machines from working because of the unavailability of these parts . Therefore, in this research we have attempted to produce curtain fabrics with 9 samples based on metallic yarns as wefts on air – jet looms with the suspension of some relay nozzles available in the machine with the use of pressure (2.5 bar), which leads to the non-consumption of relay nozzles and accessories quickly, Reduces operating cost. One of the most important results reached was that the fabrics produced by the number of 30 relay nozzles have recorded the highest readings for each of the tensile strength in the direction of the weft - weight per square meter - of fabrics produced at 40 relay nozzles and finally 50 relay nozzles that have the same operational specifications we conclude Inverse relationship between number of relay nozzles and tensile strength readings in the direction of the weft - weight per square meter - for fabrics having the same operational specifications.
Keywords: الخيوط المعدنية -- الهواء النفاث -- ماكينات النسيج -- التراكيب النسجية